ESTABLISHING A PRIORITY HIERARCHICAL FOR REGIONAL AIRPORT INFRASTRUCTURE INVESTMENTS ACCORDING TO TOURISM DEVELOPMENT CRITERIA: A BRAZILIAN CASE STUDY - A. M. Silva, Elisangela; P. Queiroz, Marcelo; A. A. S. Fortes, José (Journal of Tourism, Sustainability and Well-being, 2017)
The Brazilian government stepped up investments in works related to improving access to cities, when it was announced as the venue for the 2014 Football World Cup. The difficulties observed to guide these investments were to select regional airports of greater relevance for the tourism sector. Given the unavailability of data that could serve this purpose, the present study sought to define, from secondary and qualitative information extracted from government documents, five indicators to allow a priority hierarchical. The methodology applied the hierarchical analysis method (AHP) and standardization procedures, resulting in the selection of five airports in the North region, four airports in the Southeast, South and Northeast regions, and one in the Center-West region of Brazil. The main advantage of the methodology was the significant reduction of cost and time in the decision-making process. An important conclusion was the understanding of tourism as an option for regional economic diversification.